Design and Optimization of a Coherent Beamforming Network for an Aperiodic Concentric Ring Array - Armando Arce; Enrique Stevens-Navarro; Marco Cardenas-Juarez; Ulises Pineda-Rico; Jorge Simon; Marco A. Panduro (International Journal of Antennas and Propagation)
In this work, a flexible and reconfigurable feeding network design for a nonuniform aperture on circular concentric ring arrays is proposed and analyzed. The network subsystem delivers coherent in-phase outputs with a Gaussian-like amplitude distribution, in a modular and basic topology based on sets of alternated power combiners and dividers. A complete antenna system in a monobeam configuration with a coherent network based on grouped inputs (blocks) per ring for an aperiodic concentric ring array with beam scanning and beam shaping properties is synthesized and analyzed. Additionally, a comparative analysis based on nonuniform and uniform concentric ring arrays fed by the proposed coherent network configuration is conducted and assessed. The optimization of the aperiodic layout on the antenna aperture (radii and interelement antenna spacings) is done by the differential evolution algorithm. Numeric experimentation demonstrates the performance advantages and capabilities of the proposed coherent network configuration with a nonuniform aperture over its uniform counterpart, with an improvement in average equal to −8.7 dB of side lobe level and 3.9 dB of directivity. Furthermore, the numeric examples show a complexity reduction on the coherent feeding network configuration based on the number of control signal inputs compared with a conventional phased antenna array; in the proposed configuration, the main beam is steered and shaped with N-1 control feeding ports per ring in this antenna system.